Applications of Digital Image Processing XXVII 2004
DOI: 10.1117/12.559534
|View full text |Cite
|
Sign up to set email alerts
|

Complexity scalable motion-compensated temporal filtering

Abstract: Computer networks and the internet have taken an important role in modern society. Together with their development, the need for digital video transmission over these networks has grown. To cope with the user demands and limitations of the network, compression of the video material has become an important issue. Additionally, many video-applications require flexibility in terms of scalability and complexity (e.g. HD/SD-TV, video-surveillance). Current ITU-T and ISO/IEC video compression standards (MPEG-x, H.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The profiling results showed that the complete-to-overcomplete discrete wavelet transform is responsible for about half of the total memory accesses performed by the codec. Thus the conclusion can be drawn that, in order to support a broad set of "complexity profiles" in the IBMCTF architecture, extensive memory optimizations need to be performed on the CODWT module [15]. Finally, an important aspect that needs to be investigated is how to achieve complexity scalability in the CODWT.…”
Section: Identification Of Complexity Bottlenecksmentioning
confidence: 98%
See 1 more Smart Citation
“…The profiling results showed that the complete-to-overcomplete discrete wavelet transform is responsible for about half of the total memory accesses performed by the codec. Thus the conclusion can be drawn that, in order to support a broad set of "complexity profiles" in the IBMCTF architecture, extensive memory optimizations need to be performed on the CODWT module [15]. Finally, an important aspect that needs to be investigated is how to achieve complexity scalability in the CODWT.…”
Section: Identification Of Complexity Bottlenecksmentioning
confidence: 98%
“…Extensive experimental results are reported in [15]. The profiling results showed that the complete-to-overcomplete discrete wavelet transform is responsible for about half of the total memory accesses performed by the codec.…”
Section: Identification Of Complexity Bottlenecksmentioning
confidence: 98%